2020
DOI: 10.3390/ijerph17041387
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Activity, Diet, Weight Status and Substance Abuse on Students’ Self-Perceived Health

Abstract: The objective of this study was to determine the level and relationship between the self-perceived health of adolescents in relation to the level of practice of physical activity, adherence to the Mediterranean diet, weight status and consumption of substance abuse, such as alcohol and tobacco. A total of 516 adolescent students between the ages of 12 and 16 completed a series of questionnaires to assess their health, physical activity, compliance with the Mediterranean diet and alcohol and tobacco consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 64 publications
8
17
0
9
Order By: Relevance
“…A total of 26.6% and 16.9% of participants in this study were overweight and obese, respectively. This shows that almost half of the study sample demonstrated values related to obesity, which agrees with other studies [ 21 , 47 , 48 ]. Even though the participants were physically active, these results may be due to the influential and combination of various factors, such as inadequate daily eating patterns; increased time for sedentary behavior, characterized often as screen-based media-use behaviors [ 49 ]; not performing the minimum physical activity recommended by the WHO [ 50 ]; or insufficient sleep, which may negatively affect body weight [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…A total of 26.6% and 16.9% of participants in this study were overweight and obese, respectively. This shows that almost half of the study sample demonstrated values related to obesity, which agrees with other studies [ 21 , 47 , 48 ]. Even though the participants were physically active, these results may be due to the influential and combination of various factors, such as inadequate daily eating patterns; increased time for sedentary behavior, characterized often as screen-based media-use behaviors [ 49 ]; not performing the minimum physical activity recommended by the WHO [ 50 ]; or insufficient sleep, which may negatively affect body weight [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Results showed a positive tendency to sustain and improve patterns associated with this type of diet, given that 92.2% of our population shows moderate or optimal adherence to the MD. Therefore, a more active lifestyle is related to a higher score in the KIDMED [31,32]. Besides adherence to good eating habits, no differences were found according to gender, as previously evidenced [30], caused by context and similar lifestyle in both genders [33].…”
Section: Discussionmentioning
confidence: 72%
“…One of the main contributions of this research study is based on the relevance of adopting healthy habits for the improvement of people’s health [ 57 , 69 ] and the importance that this line of research has from an educational perspective within a Spanish and European context [ 37 , 70 ]. This research study can contribute up-to-date information that allows to draft strategies for awareness and promotion of the improvement and consolidation of healthy habits which require the cooperation of the family, the school, the social agents and the media [ 55 , 71 ].…”
Section: Resultsmentioning
confidence: 99%